SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN PESANAN MENGGUNAKAN LOAD ORIENTED MANUFACTURING CONTROL (LOMC) - Pandwinata, Deni; Purwani, Annie; Kristanto, Agung (Jurnal Ilmiah Teknik Industri, 2013)
CV. Grafika Inndah is a printing company, majoring in job order production system. While so far, the company has problems on the decision making due to lead time for booking orders that the company can accept customer orders according to quantity and due date.  The production process of the design, print finishing and that includes the print engine 52 and engine Sakura print shop.  The station receives a print job that exceeds the load capacity. Thus this research aims to determine the lead time, the average output and average utility.  Data processing in this study using the method of manufacturing systems based load control (load oriented manufacturing control), and to assist in decision-making applications built using Delphi.  Programming of the analysis of the data processing method known LOMC can the average lead time work station 2.88 hours and an average of 99.7% utilities, and Print Shop Lead time average of 1.82 hours and an average of 99.85% utilities. Decision support system applied in this study deserves to be implemented.  It can be seen from the test program using the Black Box Test and Alpha Test is evidenced in respondents answered SS (strongly agree) as much as 48% and S (agree) as much as 46% .